AMPA receptor positive allosteric modulators: a patent review. (May 2013) - Pirotte, Bernard; Francotte, Pierre; Goffin, Eric; de Tullio, Pascal
<x xml:space="preserve">Abstract</x> Introduction: AMPA receptors represent an interesting target to develop innovative therapeutic drugs such as positive allosteric modulators, a subclass of modulators known to potentiate the effect of glutamate through this kind of glutamatergic ionotropic receptors. The enhancement of AMPA signals is expected to be beneficial in the management of several neurological disorders, such as depression, schizophrenia, Parkinson's disease and learning–memory deficits linked to Alzheimer's disease. AMPA receptor positive allosteric modulators continue to be the object of intensive research as evidenced by the diversification in the range of chemotypes explored. Areas covered: This article examines recent discoveries of new AMPA receptor modulators mainly described in the patent literature from 2008 to 2012. Expert opinion: An important challenge is to discover an ideal drug candidate exhibiting appropriate in vivo activity after oral administration with an acceptable safety profile. The future remains promising because such compounds have proved to be able to stimulate the expression of the neurotrophic factor BDNF, a unique property opening interesting perspectives in new therapeutic applications.